Activation of Central Nervous System Inflammatory Pathways by Interferon-Alpha: Relationship to Monoamines and Depression - Raison, Charles L.; Borisov, Andrey S.; Majer, Matthias; Drake, Daniel F.; Pagnoni, Giuseppe; Woolwine, Bobbi J.; Vogt, Gerald J.; Massung, Breanne; Miller, Andrew H. (Biological psychiatry (1969), 2009)
Interferon (IFN)-alpha has been used to study the effects of innate immune cytokines on the brain and behavior in humans. The degree to which peripheral administration of IFN-alpha accesses the brain and is associated with a central nervous system (CNS) inflammatory response is unknown. Moreover, the relationship among IFN-alpha-associated CNS inflammatory responses, neurotransmitter metabolism, and behavior has yet to be established. Twenty-four patients with hepatitis C underwent lumbar puncture and blood sampling after ∼12 weeks of either no treatment ( n = 12) or treatment with pegylated IFN-alpha 2b ( n = 12). Cerebrospinal fluid (CSF) and blood samples were analyzed for proinflammatory cytokines and their receptors as well as the chemokine, monocyte chemoattractant protein-1 (MCP-1), and IFN-alpha. Cerebrospinal fluid samples were additionally analyzed for monoamine metabolites and corticotropin releasing hormone. Depressive symptoms were assessed using the Montgomery Asberg Depression Rating Scale. Interferon-alpha was detected in the CSF of all IFN-alpha-treated patients and only one control subject. Despite no increases in plasma IL-6, IFN-alpha-treated patients exhibited significant elevations in CSF IL-6 and MCP-1, both of which were highly correlated with CSF IFN-alpha concentrations. Of the immunologic and neurotransmitter variables, log-transformed CSF concentrations of the serotonin metabolite, 5-hydroxyindoleacetic acid (5-HIAA), were the strongest predictor of depressive symptoms. Log-transformed CSF concentrations of IL-6, but not IFN-alpha or MCP-1, were negatively correlated with log-transformed CSF 5-HIAA ( r 2 = −.25, p < .05). These data indicate that a peripherally administered cytokine can activate a CNS inflammatory response in humans that interacts with monoamine (serotonin) metabolism, which is associated with depression.